The Effectiveness of Project-Based Learning in Enhancing Speaking Skills among Senior High School Students - Siti Nur Imas; Cesa Putri Rahmadan (Journal of Applied Linguistics and Language Practice, 2025)
The study investigates the effectiveness of project-based learning (PBL) in enhancing speaking skills among senior high school students. Speaking proficiency is a critical component of language learning, yet many students face difficulties in expressing ideas fluently and confidently. This research aims to determine whether the implementation of PBL can improve students’ oral communication abilities by engaging them in collaborative, real-world tasks. A quasi-experimental design was employed, involving a sample of senior high school students divided into experimental and control groups. Data were collected through pre-tests and post-tests, along with observational checklists to evaluate students’ speaking performance. The findings reveal that students who participated in PBL demonstrated significant improvement in fluency, pronunciation, vocabulary usage, and overall confidence compared to the control group receiving conventional instruction. Moreover, PBL fostered greater student motivation, collaboration, and creativity, which contributed to the enhancement of speaking skills. The study implies that integrating project-based learning into the English language curriculum can serve as an effective strategy for promoting active learning and practical language use in classroom settings. These results provide valuable insights for educators aiming to implement innovative teaching methods to support language development.